Telehealth use in patients with type 2 diabetes in Australian general practice during the COVID-19 pandemic: a retrospective cohort study - Imai, Chisato; Thomas, Judith; Hardie, Rae-Anne; Pearce, Christopher; Badrick, Tony; Georgiou, Andrew (BJGP open, 2022)
The Australian government introduced temporary government-subsidised telehealth service items (phone and video-conference) in mid-March 2020 in response to the COVID-19 pandemic. The uptake of telehealth by patients with type 2 diabetes (T2DM) for consulting with GPs is unknown. To evaluate the uptake of telehealth consultations and associated patient characteristics in Australian general practice, including the frequency of haemoglobin A1c (HbA1c) tests and change in HbA1c levels by telehealth use, compared with guideline recommendations. This exploratory study used electronic patient data from approximately 800 general practices in Victoria and New South Wales (NSW), Australia. A pre-COVID-19 period from March 2019-February 2020 was compared with a pandemic period from March 2020-February 2021. Patients diagnosed with T2DM before March 2018 were included. Telehealth uptake patterns were examined overall and by patient characteristics. Generalised estimating equation models were used to examine patient probability of 6-monthly HbA1c testing and change in HbA1c levels, comparing between patients who did and patients who did not use telehealth. Of 57 916 patients, 80.8% had telehealth consultations during the pandemic period. Telehealth consultations were positively associated with patients with T2DM who were older, female, had chronic kidney disease (CKD), prescribed antidiabetic medications, and living in remote areas. No significant difference was found in 6-monthly HbA1c testing and HbA1c levels between telehealth users and patients who had face-to-face consultations only. Telehealth GP consultations were well utilised by patients with T2DM. Diabetes monitoring care via telehealth is as effective as face-to-face consultations.